Prolonged Use of a Continuous Peripheral Nerve Block Catheter for Analgesia after Pediatric Foot and Ankle Surgery. (21st December 2021) - MacDonald, Jake; Zhang, De-An
Abstract : Continuous peripheral nerve blocks (CPNB) have a variety of indications and have been shown to be a safe and effective means of minimizing pain postoperatively. Early studies have indicated duration of catheter use greater than 48 hours as a main contributor to infection risk in CPNBs. Recent studies, though, have suggested that the risk of infection does not increase until 4 days after insertion. In the following case report, we recount our experience in using a continuous popliteal-sciatic peripheral nerve block for postoperative pain control in a pediatric patient following calcaneal and first metatarsal osteotomy. The catheter remained in place for 65 hours postoperatively without signs of local inflammation or infection. The prolonged CPNB use resulted in a significant decrease in postoperative opioid use and pain and increase in patient satisfaction when compared to the same procedure done one year prior on the opposite foot.